The myth, the symbols and the reader in The Investigation, by Juan Jose Saer - Ramirez, Diana (Romanica Olomucensia, 2016)
This research deals with the crime novel by Juan Jose Saer La pesquisa, focusing on the reader's participation in the Argentine literary system. Another important topic is the relationship between myth and literature. The study aims to investigate the way in which Saer built his literature, since the narrative system reworks the myth through writing and leads the reader into the games and mysteries that the novel contains. The issues that this article stresses are symbols that act as vehicles for the mystery of the detective novel, such as the labyrinth, the double, and their relationship with the different levels of meaning of the novel, depending on the reader. Finally, it seeks to delve into the importance of myth in contemporary literature and developments in the narrative of this novel by Saer.
Keywords: The Investigation; Juan Jose Saer; crime novel; myth; reader; symbols; literature; double; labyrinth.